Empowering students by developing their intercultural communication competence: a two-way process - Briguglio, Carmela (ISANA International Education Association Inc., 2006)
It is a common belief that tertiary students acquire intercultural communication competence through interacting with each other in multicultural classrooms. Much research undertaken in Australia, however, indicates that having culturally diverse classrooms will not, by itself, necessarily promote student development in this area. This is particularly true of students working in multinational/multicultural teams, where often the experience can reinforce negative stereotypes instead of promoting understanding. What is required, instead, is deliberate and structured intervention promoting two-way learning not only between international and local Australian students, but also between all students of different cultural and linguistic backgrounds.This paper describes a workshop that was implemented with a group of undergraduate students at Curtin University of Technology to assist them in working successfully in multinational student teams. It will describe the activities used, not only to raise student awareness, but also to lead them to a deeper level of understanding and to develop intercultural communication competence. The paper emphasises the importance of guided discussion and how the workshop facilitator needs to lead students carefully and sensitively to explore cultural and linguistic issues in intercultural communication. The paper also discusses directions for a classroom pedagogy which utilises teaching and learning approaches that build on cultural diversity and develop intercultural communication competence in students. That is, possibilities for two-way learning in classroom contexts are explored and discussed.